Pertanggungjawaban Pidana Korporasi Dalam Pelanggaran Perlindungan Konsumen Berdasarkan Analisis Prinsip Keadilan Konsumen : Corporate Criminal Liability for Consumer Protection Violations Based on an Analysis of the Principle of Consumer Justice - Eka Erfianty Putri; Yusep Mulyana; Meitria Cahyani (Journal of Indonesian Comparative of Syari'ah Law, 2026)
The digital economic transformation and corporate dominance in market activities have increased the complexity of consumer protection violations, which can no longer be adequately addressed through civil or administrative approaches alone. The main issue in this study lies in the suboptimal construction of corporate criminal liability in ensuring justice for consumers, both in terms of determining fault and the effectiveness of the sanctions imposed. This study aims to analyse corporate criminal liability in consumer protection violations based on the principle of consumer justice, to examine the criminal sanction system applied, and to formulate measures to enhance the effectiveness of criminal law enforcement against corporations. The research method employed is a normative legal approach using both a statutory and a conceptual framework. Data was obtained through a literature review of primary, secondary, and tertiary legal sources, and subsequently analysed qualitatively using a legal-analytical method. The results of the study indicate that corporate criminal liability can be constructed through the doctrines of identification, vicarious liability, and strict liability, which are normatively capable of addressing corporate fault at both the policy and operational levels. However, its implementation still does not fully reflect the principle of consumer justice due to the predominance of criminal liability for individuals, the limitations in proving corporate fault, and the suboptimal use of criminal sanctions. The system of criminal sanctions against corporations tends to rely on fines, which in practice have not been effective without the support of additional sanctions such as restitution, revocation of business licences, and the public announcement of court rulings. This study concludes that strengthening corporate criminal liability requires an approach oriented towards consumer justice through the integration of sanctions that are repressive, preventive, and restorative in nature. The contribution of this study lies in the development of an analysis of corporate criminal law based on the principle of consumer justice as an evaluative foundation for the reform of consumer protection law in Indonesia.